PENGEMBANGAN INSTRUMEN PENILAIAN KEMAMPUAN LITERASI SAINS SISWA KELAS XI MATERI SISTEM EKSKRESI DAN KOORDINASI DI SMAN 9 MALANG - Hasana, Imroatun; Saptasari, Murni; Wulandari, Nuning (Universitas Negeri Malang, 2017)
This research was conducted to produce science literacy assessment instrument which valid (logic validity) and reliable in Excretion and Coordination topic. This research and development were use ADDIE model which consist of 5 stage (analysis, design, develop, implementation, and evaluation). Assessment instrument which developed were consist of test, nontest, and learning equipment. The subject in this research were 33 students of XI MIPA B at SMAN 9 Malang. Aspect which measured were the advisability from validator, practicability from user, and effectiveness from the students’ improvement of science literate capabilities. The research result were: advisability aspect of test and non test instrument from validator was valid. Question’s reliability of Excretion System topic was reliable enough (α = 0,547) whereas Coordination System topic was reliable (α = 0,672). Practicability aspect gained from readability and practicability result is practical. Effectiveness aspect based on Wilcoxon Signed Ranks Test result of assessment instrument base science literacy (Z quantification = 5,025), the conclusion is influence implementation of assessment instrument toward students’ science literacy accomplishment.